Teachers’ Perception on the Use of Problem-Based Learning for Teaching Reading Skills at Senior High School - Ni Kadek Siska; Abdul Kamaru ddin; Moh Abraham Akbar Eisenring; Rofiqoh Rofiqoh (Universitas Pahlawan Tuanku Tambusai, 2026)
This study examined teachers’ perceptions of the implementation of Problem-Based Learning (PBL) in teaching reading skills. Many students still struggle to comprehend texts and demonstrate low motivation during reading activities. Problem-Based Learning (PBL) is considered a suitable approach to support student-centered learning within the Merdeka Curriculum. While previous studies have discussed the effectiveness of PBL, research specifically exploring teachers’ perceptions of PBL implementation in teaching reading skills at the senior high school level remains limited. This study employed a qualitative research design. Data were collected through classroom observations and semi-structured interviews with three English teachers. The data were analyzed using the Miles, Huberman, and Saldaña model, which includes data condensation, data display, and conclusion drawing. The observation data supported the interview findings and demonstrated consistency between teachers’ perceptions and classroom teaching practices. The findings indicated that teachers held positive perceptions of PBL because this method improved students’ engagement, reading comprehension, motivation, and critical thinking skills. However, several challenges, such as time constraints and differences in students’ abilities, were also identified. Overall, the implementation of PBL was considered an effective and authentic approach to supporting the development of students’ reading skills in the context of English as a Foreign Language (EFL) education when accompanied by appropriate instructional guidance in classroom practices.